The development and testing of the psychological and behavioural resources model of team flow in project teams - Wang, Weiwei (2020)
This thesis explores the development and testing of a psychological and behavioural resources model of team flow (PBrTF) in project teams, which is a tool to promote team effectiveness, proposing that team efficacy and CZPD act as psychological and behavioural resources of team flow and that these three team level phenomena share a positive, mutually reinforcing relationships. Four studies were implemented to achieve the above-mentioned research objectives. The first study describes how team efficacy and CZPD interact to promote the emergence of team flow using a qualitative approach. The second study tests the scalability of the CZPD questionnaire, which resulted a 16-item unidimensional scale representing five aspects of an effective self-organising peer-learning entity. The third study validates the cross-time dimensional stability of the all four scales. The fourth study tests the cross-time reciprocal relationships between team efficacy, CZPD and team flow. This study also tests whether team flow antecedents mediate the effects of team efficacy and CZPD on team flow.